Unveiling Planar Defects in Hexagonal Group IV Materials - Fadaly, Elham M. T.; Marzegalli, Anna; Ren, Yizhen; Sun, Lin; Dijkstra, Alain; De Matteis, Diego; Scalise, Emilio; Sarikov, Andrey; De Luca, Marta; Rurali, Riccardo; Zardo, Ilaria; Haverkort, Jos E. M.; et al. (Nano Letters, 2021)
Recently synthesized hexagonal group IV materials are a promising platform to realize efficient light emission that is closely integrated with electronics. A high crystal quality is essential to assess the intrinsic electronic and optical properties of these materials unaffected by structural defects. Here, we identify a previously unknown partial planar defect in materials with a type I3 basal stacking fault and investigate its structural and electronic properties. Electron microscopy and atomistic modeling are used to reconstruct and visualize this stacking fault and its terminating dislocations in the crystal. From band structure calculations coupled to photoluminescence measurements, we conclude that the I3 defect does not create states within the hex-Ge and hex-Si band gap. Therefore, the defect is not detrimental to the optoelectronic properties of the hex-SiGe materials family. Finally, highlighting the properties of this defect can be of great interest to the community of hex-III-Ns, where this defect is also present.
CRIS-Team Scopus Importer:2023-04-20
Keywords: defects; hexagonal Ge; hexagonal group IV; hexagonal Si; I; Nanowires